2001
DOI: 10.1038/sj.bmt.1702798
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of a fetus with paternal Thy-1+CD34+cells for chronic granulomatous disease

Abstract: Summary:A fetus diagnosed with X-linked chronic granulomatous disease was transplanted with Thy-1 ؉ CD34 ؉ cells of paternal origin. The transplant was performed at 14 weeks gestation by ultrasound guided injection into the peritoneal cavity. The fetus was delivered at 38 weeks gestation after an otherwise uneventful pregnancy. Umbilical cord blood was collected and used to determine the level of peripheral blood chimerism as well as levels of functional engrafted cells. Flow cytometry was used to detect donor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 49 publications
0
24
0
Order By: Relevance
“…Wakabayashi et al [14] showed that GvHD also occurs in human tissue after bone marrow transplantation, particularly in areas that are not highly populated by dendritic cells. Through human cases of in utero HSCT, it is now known that the incidence of GvHD in in utero transplant models can be minimized by T-cell depletion [8,[15][16][17][18][19]. However, this comes at the expense of decreased donor cell engraftment [8,19].…”
Section: Discussionmentioning
confidence: 99%
“…Wakabayashi et al [14] showed that GvHD also occurs in human tissue after bone marrow transplantation, particularly in areas that are not highly populated by dendritic cells. Through human cases of in utero HSCT, it is now known that the incidence of GvHD in in utero transplant models can be minimized by T-cell depletion [8,[15][16][17][18][19]. However, this comes at the expense of decreased donor cell engraftment [8,19].…”
Section: Discussionmentioning
confidence: 99%
“…A number of lines of evidence point toward a lack of space in the hematopoietic tissues for donor HSCs to engraft as one possible reason for poor outcomes [1,10]. Despite the immaturity of the fetal immune system, NK cells and even T cells are present in the late first trimester fetus and may further prevent donor cell engraftment [11]. Better defining the barriers to HSC engraftment in utero is the key to improving IUT, to treat a wider range of birth defects.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the cellular immune system begins its development early in gestation around the end of the first trimester. Reports suggest that T cells can be found in liver and peripheral blood as early as 7 and 9 weeks' gestation, respectively, although their overall numbers are very low [1,2]. Intrathymic CD3…”
Section: Introductionmentioning
confidence: 99%